Oral Presentations Abstracts: FEAR OF DEATH IN MEDICAL STUDENTS 1998-2019 - ESQUERDA, Montserrat; PARRA, Ana Isabel; AGUSTÍ, Anna M.; PIFARRE, Josep (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Medical students are close in their daily work with the world of suffering and death, living with pain and loss, without having received in general any regulated preparation to face it. This lack of training is associated with a sociocultural context that avoids speaking or approaching death, making it difficult for the medical student and the professionals themselves to develop the concept of death, adequate coping strategies, talking about complex decision-making at the end of life, acceptance of limitations or more generally to palliative medicine. This fear of death can hinder ethical decision-making and end-of-life conversations. The aim of the study is to assess fear of death in a sample of medical students, from 1998 to 2019, the relationship between fear of death and age, gender, course, beliefs or experiences of death and assess the evolution of death during these 20 years. Method The study included 756 medical students, from the courses between 1998 and 2019, who were given Collet-Lester revised Scale of Fear of Death and a questionnaire of sociodemographic and biographical variables. Results The analysis of the variables surveyed indicates that medical students present an intermediate level of fear of death and the process of dying. Fear of death has increased in these decades; it also increases during medical courses. Conclusions With the results obtained, medical schools should include a more oriented a specific approach in death and suffering that allows the medical student to obtain greater knowledge and be trained in accompanying death and talking about death.